Analisis Kepuasan Customer Terhadap Produk Cokelat Almond Pada Kewirausahaan - Alfi Falah Aghnia; Rizka Inayatul Ummah; Tegar Pratama; Amin Sadiqin (CV ODIS, 2023)
Chocolate is a product made from ingredients that are very easy to find. Therefore, providing large amounts of chocolate bars can be very helpful. This way, you don't have to worry about running out of the main ingredient, which will become the most important ingredient for chocolate. Add to layer with chocolate mixture. There are still many variations and different toppings, such as almonds, walnuts, cashews, etc. Indonesia's cocoa farming industry is currently developing. Many countries in Indonesia produce nuts, especially almonds, as the primary raw material. On this occasion, the researcher hopes to create an entrepreneurial spirit with a product called